DEVELOPING BATU BELAH VOCABULARY ANIMATION VIDEO TEACHING MATERIAL FOR KINDERGARTEN - Simorangkir, Gustina; Ikhsanudin, Ikhsanudin; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
This research was conducted to fulfill the needs of kindergarten children and the English language teacher needs in teaching and learning on English vocabulary by developing teaching material entitled â€œBatu Balah animation vocabulary videoâ€. This research involved an English teacher of Bina Sari kindergarten Pontianak who taught English subject for students aged level 5 to 6 years. The method of this research was development research which consists of three phases of ADDIE (analyze, design and develop). The results of this study are learning materials for kindergarten students namely Batu Balah animation vocabulary video. Batu Balah vocabulary video is an animated video that has duration of nine minutes and twenty-one seconds and has three sections, the first section is a short animated story about Batu Balah legend, the second section is Batu Balah vocabulary video lesson and the third section is Batu Balah vocabulary activity. To complete the product of â€œBatu Balah animation vocabulary videoâ€ the researcher did the internal evaluation.Keywords: Analysis, Design, Develop, VocabularyÂ